5.17.2 Problems 101 to 200

Table 5.879: Second order, non-linear and homogeneous

#

ODE

Mathematica

Maple

8495

\[ {}2 a y^{\prime \prime }+{y^{\prime }}^{3} = 0 \]

8498

\[ {}y^{\prime \prime } = 2 {y^{\prime }}^{3} y \]

8499

\[ {}y^{\prime \prime } y+{y^{\prime }}^{3}-{y^{\prime }}^{2} = 0 \]

8501

\[ {}y^{\prime \prime } y+{y^{\prime }}^{3} = 0 \]

8503

\[ {}y^{\prime \prime } = x {y^{\prime }}^{2} \]

8504

\[ {}y^{\prime \prime } = x {y^{\prime }}^{2} \]

8505

\[ {}y^{\prime \prime } = -{\mathrm e}^{-2 y} \]

8506

\[ {}y^{\prime \prime } = -{\mathrm e}^{-2 y} \]

8507

\[ {}2 y^{\prime \prime } = \sin \left (2 y\right ) \]

8508

\[ {}2 y^{\prime \prime } = \sin \left (2 y\right ) \]

8510

\[ {}y^{\prime \prime } = {y^{\prime }}^{2} \]

8511

\[ {}y^{\prime \prime } = {\mathrm e}^{x} {y^{\prime }}^{2} \]

8512

\[ {}2 y^{\prime \prime } = {y^{\prime }}^{3} \sin \left (2 x \right ) \]

8513

\[ {}x^{2} y^{\prime \prime }+{y^{\prime }}^{2} = 0 \]

8515

\[ {}y^{\prime \prime } = \left (1+{y^{\prime }}^{2}\right )^{{3}/{2}} \]

8516

\[ {}y^{\prime \prime } y = {y^{\prime }}^{2} \left (1-y^{\prime } \sin \left (y\right )-y y^{\prime } \cos \left (y\right )\right ) \]

8517

\[ {}\left (1+y^{2}\right ) y^{\prime \prime }+{y^{\prime }}^{3}+y^{\prime } = 0 \]

8518

\[ {}\left (y^{\prime \prime } y+1+{y^{\prime }}^{2}\right )^{2} = \left (1+{y^{\prime }}^{2}\right )^{3} \]

8519

\[ {}x^{2} y^{\prime \prime } = y^{\prime } \left (2 x -y^{\prime }\right ) \]

8520

\[ {}x^{2} y^{\prime \prime } = y^{\prime } \left (3 x -2 y^{\prime }\right ) \]

8521

\[ {}x y^{\prime \prime } = y^{\prime } \left (2-3 x y^{\prime }\right ) \]

8522

\[ {}x^{4} y^{\prime \prime } = y^{\prime } \left (y^{\prime }+x^{3}\right ) \]

8525

\[ {}{y^{\prime \prime }}^{2}-x y^{\prime \prime }+y^{\prime } = 0 \]

8526

\[ {}{y^{\prime \prime }}^{3} = 12 y^{\prime } \left (x y^{\prime \prime }-2 y^{\prime }\right ) \]

8799

\[ {}y^{\prime \prime } = \frac {1}{y}-\frac {x y^{\prime }}{y^{2}} \]

8881

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }+1+x {y^{\prime }}^{2} = 1 \]

8882

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }+y {y^{\prime }}^{2} = 0 \]

8883

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }+{y^{\prime }}^{2} = 0 \]

8884

\[ {}y^{\prime \prime }+{y^{\prime }}^{2} \sin \left (y\right ) = 0 \]

8885

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }+{y^{\prime }}^{3} = 0 \]

8962

\[ {}y^{\prime \prime } = A y^{{2}/{3}} \]

8983

\[ {}y^{\prime \prime }+{\mathrm e}^{y} = 0 \]

9084

\[ {}{y^{\prime \prime }}^{2}+y^{\prime } = 0 \]

9085

\[ {}y^{\prime \prime }+{y^{\prime }}^{2} = 0 \]

9093

\[ {}{y^{\prime \prime }}^{2}+y^{\prime }+y = 0 \]

9094

\[ {}y^{\prime \prime }+{y^{\prime }}^{2}+y = 0 \]

9116

\[ {}y {y^{\prime \prime }}^{2}+y^{\prime } = 0 \]

9117

\[ {}y {y^{\prime \prime }}^{2}+{y^{\prime }}^{3} = 0 \]

9118

\[ {}y^{2} {y^{\prime \prime }}^{2}+y^{\prime } = 0 \]

9119

\[ {}y {y^{\prime \prime }}^{4}+{y^{\prime }}^{2} = 0 \]

9120

\[ {}y^{3} {y^{\prime \prime }}^{2}+y y^{\prime } = 0 \]

9121

\[ {}y^{\prime \prime } y+{y^{\prime }}^{3} = 0 \]

9122

\[ {}y {y^{\prime \prime }}^{3}+y^{3} y^{\prime } = 0 \]

9123

\[ {}y {y^{\prime \prime }}^{3}+y^{3} {y^{\prime }}^{5} = 0 \]

9124

\[ {}y^{\prime \prime }+x y^{\prime }+y {y^{\prime }}^{2} = 0 \]

9125

\[ {}y^{\prime \prime }+\sin \left (x \right ) y^{\prime }+y {y^{\prime }}^{2} = 0 \]

9126

\[ {}y^{\prime \prime }+\left (1-x \right ) y^{\prime }+y^{2} {y^{\prime }}^{2} = 0 \]

9127

\[ {}y^{\prime \prime }+\left (\sin \left (x \right )+2 x \right ) y^{\prime }+\cos \left (y\right ) y {y^{\prime }}^{2} = 0 \]

9128

\[ {}y^{\prime } y^{\prime \prime }+y^{2} = 0 \]

9129

\[ {}y^{\prime } y^{\prime \prime }+y^{n} = 0 \]

9131

\[ {}y^{\prime \prime }+\left (x +3\right ) y^{\prime }+\left (y^{2}+3\right ) {y^{\prime }}^{2} = 0 \]

9132

\[ {}y^{\prime \prime }+x y^{\prime }+y {y^{\prime }}^{2} = 0 \]

9133

\[ {}y^{\prime \prime }+\sin \left (x \right ) y^{\prime }+{y^{\prime }}^{2} = 0 \]

9134

\[ {}3 y^{\prime \prime }+\cos \left (x \right ) y^{\prime }+{y^{\prime }}^{2} \sin \left (y\right ) = 0 \]

9135

\[ {}10 y^{\prime \prime }+x^{2} y^{\prime }+\frac {3 {y^{\prime }}^{2}}{y} = 0 \]

9136

\[ {}10 y^{\prime \prime }+\left ({\mathrm e}^{x}+3 x \right ) y^{\prime }+\frac {3 \,{\mathrm e}^{y} {y^{\prime }}^{2}}{\sin \left (y\right )} = 0 \]

9159

\[ {}x^{2} y^{\prime \prime }+\left (x y^{\prime }-y\right )^{2} = 0 \]

11590

\[ {}y^{\prime \prime }-y^{2} = 0 \]

11591

\[ {}y^{\prime \prime }-6 y^{2} = 0 \]

11593

\[ {}y^{\prime \prime }-6 y^{2}+4 y = 0 \]

11596

\[ {}y^{\prime \prime }-a y^{3} = 0 \]

11600

\[ {}y^{\prime \prime }+a \,x^{r} y^{2} = 0 \]

11601

\[ {}y^{\prime \prime }+6 a^{10} y^{11}-y = 0 \]

11602

\[ {}y^{\prime \prime }-\frac {1}{\left (y^{2} a +b x y+c \,x^{2}+\alpha y+\beta x +\gamma \right )^{{3}/{2}}} = 0 \]

11603

\[ {}y^{\prime \prime }-{\mathrm e}^{y} = 0 \]

11604

\[ {}y^{\prime \prime }+a \,{\mathrm e}^{x} \sqrt {y} = 0 \]

11605

\[ {}y^{\prime \prime }+{\mathrm e}^{x} \sin \left (y\right ) = 0 \]

11606

\[ {}y^{\prime \prime }+a \sin \left (y\right ) = 0 \]

11609

\[ {}y^{\prime \prime } = \frac {f \left (\frac {y}{\sqrt {x}}\right )}{x^{{3}/{2}}} \]

11610

\[ {}y^{\prime \prime }-3 y^{\prime }-y^{2}-2 y = 0 \]

11611

\[ {}y^{\prime \prime }-7 y^{\prime }-y^{{3}/{2}}+12 y = 0 \]

11612

\[ {}y^{\prime \prime }+5 a y^{\prime }-6 y^{2}+6 a^{2} y = 0 \]

11613

\[ {}y^{\prime \prime }+3 a y^{\prime }-2 y^{3}+2 a^{2} y = 0 \]

11614

\[ {}y^{\prime \prime }-\frac {\left (3 n +4\right ) y^{\prime }}{n}-\frac {2 \left (n +1\right ) \left (n +2\right ) y \left (y^{\frac {n}{n +1}}-1\right )}{n^{2}} = 0 \]

11615

\[ {}y^{\prime \prime }+a y^{\prime }+b y^{n}+\frac {\left (a^{2}-1\right ) y}{4} = 0 \]

11616

\[ {}y^{\prime \prime }+a y^{\prime }+b \,x^{v} y^{n} = 0 \]

11618

\[ {}y^{\prime \prime }+a y^{\prime }+f \left (x \right ) \sin \left (y\right ) = 0 \]

11619

\[ {}y^{\prime \prime }+y y^{\prime }-y^{3} = 0 \]

11620

\[ {}y^{\prime \prime }+y y^{\prime }-y^{3}+a y = 0 \]

11621

\[ {}y^{\prime \prime }+\left (y+3 a \right ) y^{\prime }-y^{3}+y^{2} a +2 a^{2} y = 0 \]

11622

\[ {}y^{\prime \prime }+\left (y+3 f \left (x \right )\right ) y^{\prime }-y^{3}+y^{2} f \left (x \right )+y \left (f^{\prime }\left (x \right )+2 f \left (x \right )^{2}\right ) = 0 \]

11624

\[ {}y^{\prime \prime }+\left (y-\frac {3 f^{\prime }\left (x \right )}{2 f \left (x \right )}\right ) y^{\prime }-y^{3}-\frac {f^{\prime }\left (x \right ) y^{2}}{2 f \left (x \right )}+\frac {\left (f \left (x \right )+\frac {{f^{\prime }\left (x \right )}^{2}}{f \left (x \right )^{2}}-f^{\prime \prime }\left (x \right )\right ) y}{2 f \left (x \right )} = 0 \]

11625

\[ {}y^{\prime \prime }+2 y y^{\prime }+f \left (x \right ) y^{\prime }+f^{\prime }\left (x \right ) y = 0 \]

11628

\[ {}y^{\prime \prime }+\left (3 y+f \left (x \right )\right ) y^{\prime }+y^{3}+y^{2} f \left (x \right ) = 0 \]

11630

\[ {}y^{\prime \prime }-\left (3 y+f \left (x \right )\right ) y^{\prime }+y^{3}+y^{2} f \left (x \right ) = 0 \]

11631

\[ {}y^{\prime \prime }-2 a y y^{\prime } = 0 \]

11632

\[ {}y^{\prime \prime }+a y y^{\prime }+b y^{3} = 0 \]

11633

\[ {}y^{\prime \prime }+f \left (x , y\right ) y^{\prime }+g \left (x , y\right ) = 0 \]

11634

\[ {}y^{\prime \prime }+a {y^{\prime }}^{2}+b y = 0 \]

11635

\[ {}y^{\prime \prime }+a y^{\prime } {| y^{\prime }|}+b y^{\prime }+c y = 0 \]

11636

\[ {}y^{\prime \prime }+a {y^{\prime }}^{2}+b y^{\prime }+c y = 0 \]

11637

\[ {}y^{\prime \prime }+a {y^{\prime }}^{2}+b \sin \left (y\right ) = 0 \]

11638

\[ {}y^{\prime \prime }+a y^{\prime } {| y^{\prime }|}+b \sin \left (y\right ) = 0 \]

11639

\[ {}y^{\prime \prime }+a y {y^{\prime }}^{2}+b y = 0 \]

11640

\[ {}y^{\prime \prime }+f \left (y\right ) {y^{\prime }}^{2}+g \left (x \right ) y^{\prime } = 0 \]

11641

\[ {}y^{\prime \prime }-\frac {D\left (f \right )\left (y\right ) {y^{\prime }}^{3}}{f \left (y\right )}+g \left (x \right ) y^{\prime }+h \left (x \right ) f \left (y\right ) = 0 \]

11642

\[ {}y^{\prime \prime }+\phi \left (y\right ) {y^{\prime }}^{2}+f \left (x \right ) y^{\prime }+g \left (x \right ) \Phi \left (y\right ) = 0 \]

11643

\[ {}y^{\prime \prime }+f \left (y\right ) {y^{\prime }}^{2}+g \left (y\right ) y^{\prime }+h \left (y\right ) = 0 \]

11644

\[ {}y^{\prime \prime }+\left (1+{y^{\prime }}^{2}\right ) \left (f \left (x , y\right ) y^{\prime }+g \left (x , y\right )\right ) = 0 \]

11645

\[ {}y^{\prime \prime }+a y \left (1+{y^{\prime }}^{2}\right )^{2} = 0 \]